A Survey on Optimal Web Service selection using Quality Of Experience(QoE) (International Journal of Advanced Research in Science, Management and Technology, 2015)
Now a days it is essential to pick superiority services for service composition. Today’s Web service selection and detection approaches rely on non-functional aspects e.g., response time and availability etc. which are also known as Quality of Service (QoS). These parameters are very imperative for web service selection but it is not sure that they reflect user’s viewpoint for service selection as well as composition. In this paper we introduce a new quality attribute as a quality of experience (QoE). This new aspect depends on users experience shared when they used the web service. We propose a clarification which will automatically mines and identifies the QoE from these shared experience on Web. We judge that there is a very strong positive association between QoE and QoS. Hence QoE can be used during service selection especially when QoS data is not available or can be used as vital parameter not only for web service selection but also service composition.
Keywords: Service composition, service selection, quality of service, quality of experience, Response Time